Quality of life in children and adolescents with drug-resistant epilepsy: a single-center study in Lima, Peru - Méndez-Dávalos, Carlos (2026)
Objective: To describe the quality of life and identify its associated clinical and epidemiological factors in children and adolescents with drug-resistant epilepsy treated at a national referral center in Lima, Peru. Methods: A cross-sectional, single-center study was conducted, including patients younger than 18 years with a diagnosis of drug-resistant epilepsy, treated either on an outpatient basis or hospitalized. Quality of life was measured using the Quality of Life in Childhood Epilepsy Questionnaire (QOLCE), reported by their primary caregivers. Associations between clinical and sociodemographic variables and quality of life were evaluated using linear regression. Results: A total of 102 patients were included in the study. The mean quality-of-life score was 33.9 points, close to the minimum value of the QOLCE. In both the bivariate and multivariate models, older patient age (βa = -0.87; 95% CI: -1.60 to -0.12; p = 0.021), residing outside the capital (βa = -9.00; 95% CI: -13.00 to -4.80; p < 0.001), not attending school (βa = -14.00; 95% CI: -18.00 to -9.00; p < 0.001), having intellectual disability (βa = -16.00; 95% CI: -23.00 to -8.50; p < 0.001), and having total or partial caregiver dependence (βa = -12.00; 95% CI: -20.00 to -5.20; p < 0.001) were associated with lower quality of life. Conclusions: In this group of children and adolescents with drug-resistant epilepsy, a low quality of life was observed. Older patient age, residing outside the capital, not attending school, having intellectual disability, and having total or partial caregiver dependence were associated with lower quality of life.